Dimensiones de lo Plurinacional / Dimensions of the Plurinational - Tudela, Farit L. Rojas (Revista Direito e Práxis, 2017)
DOI: 10.1590/2179-8966/2017/31221 Resumen Propongo desarrollar 3 (tres) lecturas de lo plurinacional. La primera, relaciona dos perspectivas de lectura de lo plurinacional, que hemos denominado paralax plurinacional. Creemos de suma importancia identificar el locus de enunciación del discurso sobre lo plurinacional. La segunda lectura trata sobre la idea de producir lo común plurinacional, para ello recurrimos a la noción comunidad sin comunidad, tematizada por Jean Luc Nancy. Finalmente, a manera de cierre, y como una tercera lectura, se da cuenta de algunas incursiones jurisprudenciales sobre lo plurinacional que reflejan la tensión paralax y las posibilidades de crear lo común plurinacional. Palavras-claves: Plurinacional; Paralax; Comun; Jurisprudência. Abstract I propose to develop three (3) readings of the plurinational. The first, relates two perspectives of reading about the plurinational, which we have called plurinational paralax. We believe that it is extremely important to identify the locus of discourse enunciation on the plurinational. The second reading deals with the idea of ​​producing the plurinational common, for this we resort to the notion community without community, thematized by Jean Luc Nancy. Finally, as a closure, and as a third reading, we realize some jurisprudential incursions about the plurinational theme, that reflect the paralax tension and the possibilities of creating the plurinational common. Keywords: Plurinational; Paralax; Common; Jurisprudence.